Tuning the Dual Inhibition of Carbonic Anhydrase and Cyclooxygenase by Dihydrothiazole Benzensulfonamides - Meleddu, Rita (ACS Med Chem Lett, 2018)
[Image: see text] A novel series of of 4-[(3-phenyl-4-aryl-2,3-dihydro-1,3-thiazol-2-ylidene)amino]benzene-1-sulfonamides (EMAC10111a–g) was synthesized and assayed toward both human carbonic anhydrase isozymes I, II, IX, and XII and cyclooxygenase isoforms. The majority of these derivatives preferentially inhibit hCA isoforms II and XII and hCOX-2 isozyme, indicating that 2,3,4-trisubstituted 2,3-dihydrothiazoles are a promising scaffold for the inhibition of hCA isozymes and of hCOX-2 enzyme. The nature of the substituent at the dihydrothiazole ring position 4 influenced the activity and selectivity toward both enzyme families. EMAC10111g resulted as the best performing compound toward both enzyme families and exhibited preferential activity toward hCA XII and hCOX-2 isozymes.